2016
DOI: 10.2298/jas1603237a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and amino acid profile of differently processed feather meal

Abstract: Feather wastes represent potential alternative ingredients for animal feedstuffs which can ameliorate the protein shortage for food and feed. Previous attempts to provide information about the nutrient composition of feather meal are either too complicated for rural livestock farmers in developing countries or they provided incomplete information on chemical composition. Washed feathers were subjected to different processing techniques such as pre-soaking in distilled water, wood ash, 0.3M NaOH, a mixture of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…Crushed samples were milled using local burr mill grinder (Sule & Odugbose, 2014). Milled samples (200 g each) were subjected to Chemical treatment method with soda ash (10 % sodium ash for 60 hours at 20 °C) (AFRIS, 2012), fermentation treatment in water for 60hours (Sotolu, 2008), wood ash fermentation treatment (Adejumo et al, 2016) 10 % wood ash water for 60 hours, autoclave treatment only (Omitoyin, 1995) in autoclave machine Model YX-280A for 1 hour at 150 psi and raw unprocessed hoof (Owen et al, 1953a). All n = 5 samples were boiled for one hour (AFRIS, 2012) with the exception of autoclave treatment and oven dried at 50 o C for 8 hours.…”
Section: Collection and Processing Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crushed samples were milled using local burr mill grinder (Sule & Odugbose, 2014). Milled samples (200 g each) were subjected to Chemical treatment method with soda ash (10 % sodium ash for 60 hours at 20 °C) (AFRIS, 2012), fermentation treatment in water for 60hours (Sotolu, 2008), wood ash fermentation treatment (Adejumo et al, 2016) 10 % wood ash water for 60 hours, autoclave treatment only (Omitoyin, 1995) in autoclave machine Model YX-280A for 1 hour at 150 psi and raw unprocessed hoof (Owen et al, 1953a). All n = 5 samples were boiled for one hour (AFRIS, 2012) with the exception of autoclave treatment and oven dried at 50 o C for 8 hours.…”
Section: Collection and Processing Of Samplesmentioning
confidence: 99%
“…The processing methods used in this study compared to (Owen et al, 1953a;Falaye, 1982;Omitoyin, 1995;Coward-kelly et al, 2006;Sotolu, 2008). Feather meal (Adejumo et al, 2016) was also subjected to wood ash processing method. These were carried out in order to break the disulphide bond which makes keratin product protein unavailable for usage by livestock.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…It was observed that enzyme-degraded feather meal did not lead to organ inflammation or colour change in the experimental animals which is an indication that the test ingredients are safe for poultry consumption. The imbalance in amino acid profile of feather meal may be responsible for the variation in performance of broilers (Ochetim, 1993;Adejumo et al, 2016), which immobilised enzyme has helped to enhance. However, studies with longer duration may shed more light on this.…”
Section: Discussionmentioning
confidence: 99%
“…Feather meal is rich in cysteine but limited in methionine and lysine contents (Adejumo et al, 2016). Cysteine is however considered as an important amino acid when processing feather processing (Papadopoulus et al, 1985;Moritz and Latshaw, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation